Synthesis and Photometric Properties of SrAl2O4: Gd3+ Nanophosphors via Solution Combustion Method. (2017) - Ashwini, K.R.; Premkumar, H.B.; Darshan, G.P.; Nagabhushana, H.; Sharma, S.C.; Prashantha, S.C.; Nagaswarupa, H.P.
Abstract: A novel SrAl2 O4 : Gd 3+ (1- 11 mol%) nanophosphor were synthesized via solution combustion method by using ODH as a fuel. The synthesized samples were well characterized by Powder X-ray diffraction (PXRD), Scanning Electron Microscopy (SEM), Diffuse Reflectance spectroscopy (DRS) and PL studies. The PXRD profile of samples was matched with JCPDS No. 34–0379. From DRS, the optical energy gap of nanophosphors were calculated and found to be ∼ 3.28 - 3.38 eV. SEM images clears that particles were flakes like structure with agglomeration. PL emission spectra excited at λExc = 275 nm, exhibit intense emission peak at 312 nm along with weak peak at 306 nm were attributed to the transition of 8S7/2→6PJ (J = 7/2, 5/2) of Gd 3+ ions. The CIE (International Commission on Illumination) parameters were calculated using spectral energy distribution functions. Photometric characterization indicated the suitability of SrAl2 O4 : Gd 3+ phosphor for pure white color. These results suggesting that the SrAl2 O4 : Gd 3+ phosphors may be a promising component for cost-effective near UV light emitting diodes (NUV-LEDs).